Pedagogical interventions and their influences on university-level students learning pharmacology-a realist review - Khurshid, Faraz; O’Connor, Elizabeth; Thompson, Rachel; Hegazi, Iman (Frontiers in Education, 2023)
troublesome content, traditional delivery methods, inadequate and limited opportunities for knowledge integration, and application. Active participation in interactive learning, along with enjoyment and motivation, was proposed as a causal mechanism for optimising cognitive load and achieving positive outcomes. The outcomes of the review include subjective perceptions of improved confidence and satisfaction, objective measurements of high post-test scores.Pedagogical scaffolding in constructivist learning environments helps students overcome challenges in learning troublesome pharmacology knowledge. Considering the human cognitive system's processing capacity, these interventions improve learning by effectively using cognitive resources. Innovations that focus on enhancing cognitive load through task construction can also promote positive emotional experiences in students, such as engagement and enjoyment, as explained by flow theory. A constructive learning environment, where the cognitive load is optimised and high flow is achieved, can maximise the impact of pedagogical interventions in pharmacology.